Tryptophan breakdown and cognition in bipolar disorder. (July 2017) - Platzer, Martina; Dalkner, Nina; Fellendorf, Frederike T.; Birner, Armin; Bengesser, Susanne A.; Queissner, Robert; Kainzbauer, Nora; Pilz, René; Herzog-Eberhard, Simone; Hamm, Carlo; Hörmanseder, Christa; Maget, Alexander; et al.
Highlights: Cognitive deficits contribute to the large burden of illness associated with bipolar disorder. Chronic inflammation in the CNS results in alterations in neural structures that subserve cognitive function. An imbalance towards neurotoxic TRYCATs may be involved in the development of structural abnormalities. In males with a higher 3-hydroxykynurenine/kynureninc acid ratio was associated with poorer verbal memory performance. The correction of these inflammatory alterations may constitute a potential therapeutic target. Abstract: Introduction: It has been demonstrated that bipolar disorder (BD) is often accompanied by cognitive deficits across all subdomains including verbal memory, attention and executive functioning. Cognitive deficits are observed both during episodes of mania or depression, as well as during the euthymic phase. It has been proposed that chronic immune-mediated inflammation in the central nervous system results in alterations in neural structures that subserve cognitive function. Kynurenine is an intermediate in the inflammatory cascade and can be peripherally measured to proxy inflammatory activity. Herein, we sought to determine whether serum levels of kynurenine and/or its metabolites were associated with cognitive function in BD. Methods: In this investigation 68 euthymic individuals with BD according to DSM-IV completed a cognitive test battery to asses premorbid intelligence (Multiple Choice Word Test; MWT-B), verbal memory (California Verbal Learning Test; CVLT), attention (d2 Test of Attention; d2 test, Trail Making Test-A; TMT-A, Stroop word reading/Stroop color naming) and executive functioning (TMT-B, Stroop interference). In addition, fasting blood samples were taken and serum levels of kynurenine and its metabolites 3-hydroxykynurenine and kynurenic acid were analyzed. Subsequently ratios were formed from individual parameters. Patient data were compared with those of a mentally healthy control group (n = 93). Results: In male participants with BD only we found a significant negative correlation between the 3-hydroxykynurenine to kynurenic acid ratio and performance on the CVLT. Additionally, the kynurenine to 3-hydroxykynurenine ratio was associated with performance on a sub-score of the CVLT. Those associations were neither present in female individuals with BD nor in the control group. Discussion: Our findings suggest that a shift towards the hydroxykynurenine arm of the kynurenine pathway may be associated with poorer memory performance due to its effects on neuronal functioning and neurogenesis in the hippocampus. Our results implicate a mechanistic role of central inflammatory processes in cognitive functions in adults with bipolar disorder.